Analysis of consumers purchase intention in commerce and services in the neighborhood and the Impact of Covid-19 - Aragão, Claudia Gomes de [UNESP]; Ferreira, Flavio Mangili; Silva, Hermes Moretti Ribeiro da [UNESP]; Belé, Tiago Gomes de Aragão (FapUNIFESP (SciELO), 2024)
Paper aims: To analyze the consumers intention to buy in commerce and services in the neighborhood, using the Theory of Planned Behavior (TPB) as a theoretical basis, analyzing the Attitude, the Subjective Norm, the Perceived Behavioral Control, and expanding the TPB through the influence on the Attitude of the Moral Attitude, Empathic Concern and the Impact of Covid-19. Originality: There are no studies on consumer buying behavior in commerce and neighborhood services in emerging countries, nor with this combination in the conceptual structure - TBP, Empathic Concern, Moral Attitude and the Impact of Covid-19. Research method: Data were collected from respondents, and analysis was performed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). Main findings: The results indicate that the consumer's attitude towards buying in the neighborhood's commerce and services was positively and significantly influenced by the Moral Attitude and Impact of Covid-19 but not by Empathic Concern. Attitude, Subjective Norm, and Perceived Behavioral Control positively and significantly influence the intention to buy in neighborhood commerce and services. Implications for theory and practice: As a theoretical implication, the conceptual model extends the TBP, adding the dimensions of Empathic Concern, Moral Attitude, and the Impact of Covid-19 on Attitude. In practice, the study can help store managers, retailers, and marketing professionals in the sector incorporate specific actions to reach potential consumers and improve their results.
Keywords: Buy intention; Covid-19; Local service; Neighborhood economy; Theory of planned behavior